Trichoderma pers. ex fr. and its efficacy as a biological control agent of basal stem rot of oil palm (Elaeis guineensis jacq.) - Ilias, G. N. M. (2000)
This study evaluated the potential of species of Trichoderma as a bio-control agent against Ganoderma boninense Pat., the causal pathogen of 'basal stem rot' of oil palms. Out of 102 Trichoderma colony-forming units (CFU) isolated from oil palm rhizospheres, 39 were T. harzianum Rifai, 38 were T. aureoviride Rifai, 19 were T. longibrachiatum Rifai and 5 were T. virens (Miller, Giddens and A. A. Foster) von Arx. Isolate T43 showed overlapping characteristics between T. hamatum and T. harzianum and was termed 'indeterminable' taxonomically. All isolates were screened for their antagonistic properties against G. boninense (isolate PP28) by dual culture studies, from which isolates T32 (T. harzianum) and T128 (T. virens) were selected as the two most effective antagonists. In vitro non-mycelial studies by normal and bilayer poison agar techniques and of culture filtrates, showed that secondary metabolites produced by the two selected isolates were able to suppress growth of Ganoderma on agar as well. In greenhouse trials using Trichoderma-incorporated mulch, all 5 control plants were killed by Ganoderma at 24 weeks after infection, whereas the survival rates were 60% and 20% when treated with T32 and T128 respectively. These were 80% for T32 and 40% for T128 using clonal plants for the same experiment. Two out of 4 modes showed very good disease control when Trichoderma was used as conidial suspension. As a root coating supplemented by Trichoderma-incorporated mulch at the start of experiment, the survival rate was 90% when treated with T32 and 70% with T128. When applied directly (1 L/plant once every fortnight for 12 weeks), a survival rate of 90% using T32 and 80% using T128 were obtained. In the use of its secondary metabolites, 2 out of 3 modes of application gave very good results. The first was by direct application of secondary metabolites (300 ml/plant at fortnightly intervals for 6 times), which resulted in a survival rate of 70% when treated with T32 and 60% when treated with T128. The second was its application as root coating followed by a single boost of 300 ml of the metabolite given only once at the start of the experiment, which resulted in a survival rate of 70% using T32 and 40% using T128. Trichoderma treatments were found to be effective when applied at the start of experiment but were no longer effective in delayed treatments of 6 to 8 weeks after infection. T32 (T. harzianum) showed better efficacy than T128 (T. virens) for all experiments. Trichoderma treatments which gave good survival rates and which could be commercially exploited were its use in the form of conidial suspension, whether applied indirectly as a root coating or poured directly on to soils of infected plants.